2006
DOI: 10.1158/1078-0432.ccr-05-1699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the expression and prognostic significance of differentiation markers between diffuse large B-cell lymphoma of central nervous system origin and peripheral nodal origin.

Abstract: Purpose: Whether diffuse large B-cell lymphoma (DLBCL) of primary central nervous system origin (PCNSL) is biologically different from DLBCL of peripheral nodal origin (NL) remains unclear. The purpose of this study was to compare the expression frequencies and prognostic significance of a panel of cell differentiation markers between these two disease entities. Experimental Design:This study included HIV-unrelated patients with PCNSL (n = 51) and NL (n = 72) treated at four hospitals inTaiwan for whom archiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 27 publications
(24 reference statements)
5
87
3
Order By: Relevance
“…Harada et al, 1999;Braaten et al, 2003;Berglund et al, 2005;Sjo et al, 2007), whereas nine studies did not report any significant difference in OS between positive and negative BCL-6 expression in DLBCL patients (e.g. Colomo et al, 2003;Kojima et al, 2006;Lin et al, 2006;Muris et al, 2006). A study by Winter et al (2006), reported a significantly increased OS in DLBCL patients with positive BCL-6 expression that were treated with the CHOP regimen, but no difference in OS related to BCL-6 expression in patients treated with R-CHOP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Harada et al, 1999;Braaten et al, 2003;Berglund et al, 2005;Sjo et al, 2007), whereas nine studies did not report any significant difference in OS between positive and negative BCL-6 expression in DLBCL patients (e.g. Colomo et al, 2003;Kojima et al, 2006;Lin et al, 2006;Muris et al, 2006). A study by Winter et al (2006), reported a significantly increased OS in DLBCL patients with positive BCL-6 expression that were treated with the CHOP regimen, but no difference in OS related to BCL-6 expression in patients treated with R-CHOP.…”
Section: Discussionmentioning
confidence: 99%
“…Of these studies, six reported significant association between positive MUM-1 expression and decreased OS (Chang et al, 2004;Hans et al, 2004;Lin et al, 2006;Muris et al, 2006;Hallermann et al, 2007;Liu et al, 2008), while ten failed to find a significant difference in OS between patients with positive and negative MUM-1 expression (e.g. Berglund et al, 2005;Kojima et al, 2006;Oh and Park, 2006;Sjo et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 The clinical behavior and prognosis of these lymphomas is not only influenced by the anatomic location but apparently also by biological factors (ABC-like versus GCB-like tumors with different underlying oncogenic mechanisms). Immunohistochemical expression of bcl-6 in PCNSL is found to be associated with a longer OS.…”
Section: Dlbcl With Plasmablastic Morphologymentioning
confidence: 99%
“…6,13 A number of studies have shown expression of Bcl-6 protein in most diffuse large B-cell PCNSLs. 6,26,27 A majority (85%) also are positive for an activation marker of late germinal center/early postgerminal center B cells (MUM-1). 6,27 A few expressed vs38c, a marker for plasma cells, but all were negative for CD138, another marker of plasmacytic differentiation.…”
Section: Molecular Studiesmentioning
confidence: 99%